Formation of College Plans: Expected Returns, Preferences and Adjustment Process - Ghazala Azmat; Katja Maria Kaufmann (Institute of Labor Economics (IZA), 2021)
We exploit a large exogenous shock to study the determinants of college attendance and the role played by one's environment. We analyze whether, and how quickly, adolescents' college plans are adapted, explore factors leading to the adjustment, and examine how these factors ultimately impact later educational attainment. Using differences across East German cohorts induced by the timing of the German Reunification (a change for the East from state socialism to capitalist democracy), we show that shortly after relative to before that time, college plans among high-school students increased substantially, which was followed by sizable increases in the completion of the college entrance certificate five years later. Our analysis sheds light on the elasticity of beliefs and preferences of different cohorts of youths in the case of a large shock. Perceived educational returns, economic preferences ("consumerism") and sociopolitical attitudes ("individualism") adapt quickly in response to the shock and are directly linked to changes in plans and outcomes. Cohorts closer to critical educational junctions at the time of Reunification, however, adjusted their plans to a much lesser extent. While they similarly updated the expected returns to education, they exhibited a slower adjustment in their preferences relative to younger cohorts.
Keywords: I21; D72; D91; 330; college plans; perceived returns; economic; social and political preferences